PENGARUH JALAN KAKI TERHADAP PENURUNAN KADAR GULA DARAH PADA LANSIA PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KUTABUMI TAHUN 2022 - Fitria Nur Rizki; Alfika Safitri; Rina Puspita Sari (Nusantara Hasana Journal, 2022)
Diabetes Mellitus is a disease characterized by high blood sugar levels in the urine due to metabolic disorders because the production and function of the hormone insulin does not work properly. Physical exercise that can be done is to walk for 30 minutes for 3x in a row in 2 weeks. Objective of the study conducted to identify the effect of walking on the decrease in blood sugar levels in elderly people with Type 2 Diabetes Mellitus. This type of research uses a pre-experimental method, a One Group Pre-Post Test Design approach. The sample of this study was 35 elderly respondents of Type 2 Diabetes Mellitus in the Kutabumi Area, Pasar Kemis District, Tangerang Regency. Male gender around 15 respondents (42.9%) and female gender around 20 respondents (57.1%). The result of the p value of 0.000 means (p<α = 0.05) which means that there is an influence of walking on the decrease in blood sugar levels. There is an effect of Walking on Reducing Blood Sugar Levels in Elderly People with Type 2 Diabetes Mellitus in the Kutabumi Area, Pasar Kemis District, Tangerang Regency.